Adult attachment in eating disorders mediates the association between perceived invalidating childhood environments and eating psychopathology - Gonçalves, Sónia (2019)
This study aimed to evaluate the associations between perceived invalidating childhood environments, attachment in intimate relationships and eating psychopathology, to explore how these variables interact with each other, and to explore potential mediators to this pattern of association in a clinical eating disorder (ED) sample. One hundred thirty-seven ED outpatients were evaluated with the Invalidating Childhood Environments Scale (ICES), the Eating Disorder-15 (ED-15) and the Experiences in Close Relationships Inventory (ECR). Paternal invalidation was associated to the ED-15 total score through avoidance of proximity and anxiety over abandonment, while maternal invalidation was only associated to the ED-15 total score through avoidance of proximity. Our results highlight the potential role of the perception of an invalidating family environment in the development of eating pathology and of difficulties in intimate relationships. These results endorse the relevance of address parental invalidation and promote adequate emotion regulation strategies and interpersonal competencies in the context of intimate relationships.